Linker dependent intercalation of bisbenzimidazole-aminosugars in an RNA duplex; selectivity in RNA vs. DNA binding. Issue 24 (15th December 2016) - Ranjan, Nihar; Arya, Dev P.
Graphical abstract: Abstract: Neomycin and Hoechst 33258 are two well-known nucleic acid binders that interact with RNA and DNA duplexes with high affinities respectively. In this manuscript, we report that covalent attachment of bisbenzimidazole unit derived from Hoechst 33258 to neomycin leads to intercalative binding of the bisbenzimidazole unit (oriented at 64–74° with respected to the RNA helical axis) in a linker length dependent manner. The dual binding and intercalation of conjugates were supported by thermal denaturation, CD, LD and UV–Vis absorption experiments. These studies highlight the importance of linker length in dual recognition by conjugates, for effective RNA recognition, which can lead to novel ways of recognizing RNA structures. Additionally, the ligand library screens also identify DNA and RNA selective compounds, with compound9, containing a long linker, showing a 20.3 °C change in RNA duplexTm with only a 13.0 °C change inTm for the corresponding DNA duplex. Significantly, the shorter linker in compound3 shows almost the reverse trend, a 23.8 °C change in DNATm, with only a 9.1 °C change inTm for the corresponding RNA duplex.